2017
DOI: 10.1038/s41598-017-15644-7
|View full text |Cite
|
Sign up to set email alerts
|

Limited evidence of declining growth among moisture-limited black and white spruce in interior Alaska

Abstract: Boreal forests play critical roles in global carbon, water and energy cycles. Recent studies suggest drought is causing a decline in boreal spruce growth, leading to predictions of widespread mortality and a shift in dominant vegetation type in interior Alaska. We took advantage of a large set of tree cores collected from random locations across a vast area of interior Alaska to examine long-term trends in carbon isotope discrimination and growth of black and white spruce. Our results confirm that growth of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 60 publications
10
43
0
Order By: Relevance
“…Our findings that growth declined with increasing moss depth and showed greater declines in high conifer BA than low conifer BA stands in warm, dry summers suggest that if factors related to succession and tree age are not accounted for, the result will likely be declining spruce radial growth rates over time and it will not be possible to discern whether this is due to climate changes, succession, tree aging, or some combination thereof. This accords with the finding that detrending methods influence the apparent growth trends in white and black spruce (Sullivan et al, ; Sullivan, Pattison, Brownlee, Cahoon, & Hollingsworth, ). It is important to note that we did not explicitly examine trends over time in this paper, but found that site factors that do change over time significantly influence white spruce climate‐growth responses.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings that growth declined with increasing moss depth and showed greater declines in high conifer BA than low conifer BA stands in warm, dry summers suggest that if factors related to succession and tree age are not accounted for, the result will likely be declining spruce radial growth rates over time and it will not be possible to discern whether this is due to climate changes, succession, tree aging, or some combination thereof. This accords with the finding that detrending methods influence the apparent growth trends in white and black spruce (Sullivan et al, ; Sullivan, Pattison, Brownlee, Cahoon, & Hollingsworth, ). It is important to note that we did not explicitly examine trends over time in this paper, but found that site factors that do change over time significantly influence white spruce climate‐growth responses.…”
Section: Discussionsupporting
confidence: 88%
“…We then subtracted the mean monthly vapor pressure (VAP) value to obtain mean monthly vapor pressure deficit (VPD = SVP − VAP). Nonlinear climate‐growth relationships have been found for white spruce (D'Arrigo et al, ; Lloyd et al, ; Nicklen et al, ; Sullivan et al, ; Wilmking et al, ); thus, we included nonlinear (quadratic) VPD terms (Table ). As gridded precipitation data can be imprecise (McAfee et al, ), we included only linear precipitation–growth relationships to minimize detecting spurious precipitation–growth relationships.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…) and (3) the Fairbanks summer air temperature record is well‐correlated with records from other stations throughout interior Alaska and western Canada (Sullivan et al. ). Ring width indices were assessed for their correlation with mean monthly air temperature and total monthly precipitation during the growing season (May–August) for the growth year and the year prior to ring formation using the treeclim package in R. Significant correlations (α = 0.05) between climate and tree‐ring indices were determined using “stationary” bootstrap resampling (1,000 iterations).…”
Section: Methodssupporting
confidence: 52%
“…One of the most reliable sources of long-term climate data for interior Alaska is the record for Fairbanks, AK , which we obtained from the Alaska Climate Research Center. Although cores were collected throughout the 922,00 ha of forested land in the Tanana Valley State Forest and the Tetlin National Wildlife Refuge, we elected not to use data from additional locations in climate-growth analyses because (1) most stations have short and/or incomplete records, (2) gridded precipitation data for Alaska are plagued by temporal inhomogeneities associated with differences in record length across stations (McAfee et al 2014) and (3) the Fairbanks summer air temperature record is well-correlated with records from other stations throughout interior Alaska and western Canada (Sullivan et al 2017). Ring width indices were assessed for their correlation with mean monthly air temperature and total monthly precipitation during the growing season (May-August) for the growth year and the year prior to ring formation using the treeclim package in R. Significant correlations (a = 0.05) between climate and tree-ring indices were determined using "stationary" bootstrap resampling (1,000 iterations).…”
Section: Climate-growth Relationships Among Speciesmentioning
confidence: 99%